Methylenedioxypyrovalerone (MDPV) mimics cocaine in its physiological and behavioral effects but induces distinct changes in NAc glucose - Wakabayashi, Ken T.; Ren, Suelynn E.; Kiyatkin, Eugene A. (Frontiers in Neuroscience, 2015)
Methylenedioxypyrovalerone (MDPV) is generally considered to be a more potent cocaine-like psychostimulant, as it shares a similar pharmacological profile with cocaine and induces similar physiological and locomotor responses. Recently, we showed that intravenous cocaine induces rapid rise in nucleus accumbens (NAc) glucose and established its relation to neural activation triggered by the peripheral drug actions. This study was conducted to find out whether MDPV, at a behaviorally equivalent dose, will share a similar pattern of NAc glucose dynamics. Using enzyme-based glucose sensors coupled with amperometery in freely moving rats, we found that MDPV tonically decreases NAc glucose levels, a response that is opposite to what we previously observed with cocaine. By analyzing Skin-Muscle temperature differentials, a valid measure of skin vascular tone, we found that MDPV induces vasoconstriction; a similar effect at the level of cerebral vessels could be responsible for the MDPV-induced decrease in NAc glucose. While cocaine also induced comparable, if not slightly stronger peripheral vasoconstriction, this effect was overpowered by local neural activity-induced vasodilation, resulting in rapid surge in NAc glucose. These results imply that cocaine-users may be more susceptible to addiction than MDPV-users due to the presence of an interoceptive signal (i.e. sensory cue), which may result in earlier and more direct reward detection. Additionally, while health complications arising from acute cocaine use are typically cardiovascular related, MDPV may be more dangerous to the brain due to uncompensated cerebral vasoconstriction.